Getting the strain under control: Trans-Varestraint tests for hot cracking susceptibility - Statharas, Dimitrios; Atkinson, Helen; Thornton, Rob; Marsden, John; Dong, Hongbiao; Wen, Shuwen (Springer, 2019)
A new method for conducting Trans-Varestraint tests for assessing hot cracking susceptibility is proposed. Experiments were carried out, to validate the new method, with an industrial scale rig using tungsten inert gas welding. The hot cracking susceptibility of API-5L X65 and EN3B steel was compared. The results indicated that, by using the new method, the strain applied to the welding bead and consequently to the solidification front was controlled in a repeatable and reliable way. The results also indicated that EN3B has a maximum crack length (a parameter in the test) higher than X65 and it is reached at lower augmented strain thus demonstrating it is more susceptible to hot cracking, while also indicating that there is a capability of predicting the initiation position of hot cracks during welding. By using the method proposed, the capability of setting standardized test procedures for Trans-Varestraint tests is improved. It is recommended that future tests for assessing hot cracking susceptibility should employ the proposed method in order for the results to be comparable and to also study the effect of strain rate in hot cracking of materials.
Keywords: hot cracking susceptibility; Trans-Varestraint test; hot cracks; steels; testing standards